Classification of regional labour markets for purposes of research and of labour market policy - Uwe Blien; Franziska Hirschenauer; Van Phan thi Hong (European Regional Science Association (ERSA), 2005)
In many countries labour market policy has to deal with fairly large and persistent regional labour market disparities. In the case of Germany, parts of the country are affected by a deep unemployment crisis whereas others show nearly full employment. Since these disparities cannot be reduced to only one dimension a classification system of labour markets was developed. The criterion of this system was the identification of the "regional disadvantage” for the success of labour market policy. To optimise the results a new two-step classification method was applied. The first step included re-gression analyses to identify the exogenous determinants of the success of labour market policy. In the second step, different types of labour markets are determined from a specific variant of cluster analysis which used the weighted variables identified as significant in the first step. This classification has been used in the Federal Employment Agency for many applications of labour market policy, e.g. in the decentralised management. Besides that, the new classification obtained has also been employed in research, for example in the evaluation of labour market policy.
Keywords: 330